2014
DOI: 10.1016/j.imlet.2014.04.012
|View full text |Cite
|
Sign up to set email alerts
|

The yin-yang of long pentraxin PTX3 in inflammation and immunity

Abstract: Pentraxins are a family of multimeric proteins characterized by the presence of a pentraxin signature in their C-terminus region. Based on the primary structure, pentraxins are divided into short and long pentraxin: C-reactive protein (CRP) is the prototype of the short pentraxin subfamily while pentraxin 3 (PTX3) is the prototypic long pentraxin. Despite these two molecules exert similar fundamental actions in the regulation of innate immune and inflammatory responses, several differences exist between CRP an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 84 publications
(97 reference statements)
4
71
0
1
Order By: Relevance
“…PTX3 deficiency causes a reduced immune response to pathogens and increases tissue damage in ischemic myocardium and atherosclerotic lesions (see Daigo et al [2014] for a more detailed description of the Ptx3 À/À mouse phenotype). Also, recent observations have shown that the growth of chemical carcinogen-induced skin tumors is delayed in these animals (Bonavita et al, 2015).…”
Section: Generation Of Transgenic Hptx3-expressing Tgn(tie2-hptx3) Micementioning
confidence: 99%
“…PTX3 deficiency causes a reduced immune response to pathogens and increases tissue damage in ischemic myocardium and atherosclerotic lesions (see Daigo et al [2014] for a more detailed description of the Ptx3 À/À mouse phenotype). Also, recent observations have shown that the growth of chemical carcinogen-induced skin tumors is delayed in these animals (Bonavita et al, 2015).…”
Section: Generation Of Transgenic Hptx3-expressing Tgn(tie2-hptx3) Micementioning
confidence: 99%
“…CRP is the prototype of the short pentraxin subfamily and pentraxin-3 (PTX-3) belongs to the long pentraxin family. PTX-3 is a multimeric acute phase inflammatory glycoprotein in the same family as CRP, a well-known cardiovascular biomarker (11). Its secretion is stimulated in endothelial cells, macrophages, myeloid cells, and dendritic cells by cytokines and endotoxins.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the experiments investigating the effects of PTX3 on whole blood coagulation, 0.25 µg/mL of PTX3 indeed exerted some procoagulant activity, although it was not statistically significant (the activity increase became significant when 1.0 µg/mL PTX3 was used). However, considering that PTX3 levels in the circulating blood increase to 1.5 µg/mL under inflammatory conditions [42], the maximum levels at an inflammatory site might be several times higher than those in the circulating blood, and possibly beyond the concentration used in the experiments. We therefore believe that the PTX3 concentrations used in the current study are clinically relevant.…”
Section: Discussionmentioning
confidence: 99%